CHARACTERIZATION OF FLUORO-EDENITE BY μ-RAMAN AND μ-FTIR SPECTROSCOPY - Rinaudo C.; Cairo S.; Gastaldi D.; Gianfagna A.; Tagliani S.M.; Tosi G.; Conti C. (My University, 2006)
The prismatic variety of fluoro-edenite, a new amphibole found in lavas from Mt Etna in Biancavilla (Catania Province, Sicily, Italy), has been characterized by μ-Raman and μ-FTIR spectroscopy. The wavenumbers at which the bands are detected in the μ-Raman and μ-FTIR spectra are compared with tremolite, asbestos the chemical and crystallographic characteristics of which are very similar to those of fluoro-edenite. © 2006 The Mineralogical Society.
Keywords: FLUORO-EDENITE; IR SPECTROSCOPY; RAMAN SPECTROSCOPY; TREMOLITE